Crystal structures of ABL-related gene (ABL2) in complex with imatinib, tozasertib (VX-680), and a type I inhibitor of the triazole carbothioamide class. - Salah, E; Ugochukwu, E; Barr, A; von Delft, F; Knapp, S; Elkins, J (2011)
ABL2 (also known as ARG (ABL related gene)) is closely related to the well-studied Abelson kinase cABL. ABL2 is involved in human neoplastic diseases and is deregulated in solid tumors. Oncogenic gene translocations occur in acute leukemia. So far no structural information for ABL2 has been reported. To elucidate structural determinants for inhibitor interaction, we determined the cocrystal structure of ABL2 with the oncology drug imatinib. Interestingly, imatinib not only interacted with the ATP binding site of the inactive kinase but was also bound to the regulatory myristate binding site. This structure may therefore serve as a tool for the development of allosteric ABL inhibitors. In addition, we determined the structures of ABL2 in complex with VX-680 and with an ATP-mimetic type I inhibitor, which revealed an interesting position of the DFG motif intermediate between active and inactive conformations, that may also serve as a template for future inhibitor design.